(untitled) (Revista Electrónica Calidad en la Educación Superior, 2018)
The purpose of this article is to share the experience of the National University of Chimborazo of Ecuador in the processes of external evaluation in terms of university teaching quality and the contribution of evaluation in the perspective of continuous improvement, but before the standars evaluation were analyzed. This study was carried out based on the evaluation report issued by the Council for Evaluation, Accreditation and Quality Assurance of Higher. Education whose instrument was the CEAACES 2012 and 2015 Evaluation Model, with a bibliographic analysis of the standars that influence in the Quality of university teachers, the essence of these and possible alternatives were raised for improvement.